2016
DOI: 10.1038/ni.3590
|View full text |Cite
|
Sign up to set email alerts
|

Heme drives hemolysis-induced susceptibility to infection via disruption of phagocyte functions

Abstract: Hemolysis drives susceptibility to bacterial infections and predicts poor outcome from sepsis. These detrimental effects are commonly considered to be a consequence of heme-iron serving as a nutrient for bacteria. We employed a Gram-negative sepsis model and found that elevated heme levels impaired the control of bacterial proliferation independently of heme-iron acquisition by pathogens. Heme strongly inhibited phagocytosis and the migration of human and mouse phagocytes by disrupting actin cytoskeletal dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 77 publications
7
102
2
Order By: Relevance
“…Intravascular hemolysis during malaria infection leads to release of the heme moiety from extracellular hemoglobin, and we speculate that heme toxicity contributes to impaired monocyte phagocytosis of IEs. This notion is supported by recent work by Martins et al, in which they demonstrate that heme inhibits phagocyte function directly by disrupting the actin cytoskeleton via interactions with DOCK8 and Cdc42 (50). In addition, increasingly impaired neutrophil phagocytosis of Salmonella was associated with increasingly severe hemolysis during malaria in Gambian children (51).…”
Section: Cd16mentioning
confidence: 71%
“…Intravascular hemolysis during malaria infection leads to release of the heme moiety from extracellular hemoglobin, and we speculate that heme toxicity contributes to impaired monocyte phagocytosis of IEs. This notion is supported by recent work by Martins et al, in which they demonstrate that heme inhibits phagocyte function directly by disrupting the actin cytoskeleton via interactions with DOCK8 and Cdc42 (50). In addition, increasingly impaired neutrophil phagocytosis of Salmonella was associated with increasingly severe hemolysis during malaria in Gambian children (51).…”
Section: Cd16mentioning
confidence: 71%
“…It is well documented that CD25 recycling participates in IL-2-mediated signaling (47,48) and that DOCK8 is also involved in cytoskeletal reorganization (49,50). The defect in IL-2 signaling observed in DOCK8-deficient Tregs could in part be due to abnormal CD25 recycling.…”
Section: Discussionmentioning
confidence: 99%
“…Haemolysis is a severe complication of sepsis that is predictive of a poor outcome 140 . Recently, haem was identified as a strong inhibitor of phago cytosis and phagocyte migration, as it disrupts actin cyto skeletal dynamics 141 . A chemical screen revealed that the common anti-malaria drug quinine could prevent the effects of haem on the cytoskeleton, restore phago cytosis and improve survival in mouse models of sepsis 141 .…”
Section: The Administration Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Recently, haem was identified as a strong inhibitor of phago cytosis and phagocyte migration, as it disrupts actin cyto skeletal dynamics 141 . A chemical screen revealed that the common anti-malaria drug quinine could prevent the effects of haem on the cytoskeleton, restore phago cytosis and improve survival in mouse models of sepsis 141 . These results suggest that quinine could be a potential therapeutic for use in selected patients with sepsis.…”
Section: The Administration Of Mesenchymal Stem Cellsmentioning
confidence: 99%